In vitro antimalarial activity of the biosurfactant produced by Serratia marcescens MBC1: Antimalarial activity from biosurfactant - Arifiyanto, Achmad; Setyaningrum, Endah; Ni'matuzahroh, Ni'matuzahroh (Iranian Journal of Pharmaceutical Sciences, 2022)
Serratia is a bacterium with a distinctive red-pigment prodigiosin, known as a plasmodium growth inhibitor. This species is also known for its reliability as a producer of biosurfactants. Furthermore, the ability of these bacteria to reduce the interface tension in antimalarial activity has not been reported. Therefore, this study aimed to develop biosurfactants as antimalarial drugs candidate. Additionally, tryptone Soy Broth is used as a fermented media to produce biosurfactants with the addition of Serratia marcescens MBC1. Biosurfactant activity was evaluated on a hydrocarbon substrate consisting of used motor lubricants, used-cooking oil, and diesel. Emulsifying activity, oil spread test, blue agar, and infrared spectroscopy were methods used for evaluating biosurfactants. Used motor lubricants produced the highest emulsification index at 41.40%. Spectroscopic results using Fourier-transform infrared spectroscopy (FTIR) revealed that the compounds contain glycolipids and lipopeptides. The antimalarial test using Plasmodium falciparum d37 obtained an inhibitory concentration 50 of 3.66 µg/mL. There was limited information on the toxicity of biosurfactants in cells of Plasmodium parasites. The use of biosurfactants from Serratia marcescens MBC1 to control plasmodium infection needs to be improved to provide an alternative to malaria control from natural ingredients.